2015
DOI: 10.7554/elife.03952
|View full text |Cite
|
Sign up to set email alerts
|

Widespread correlation patterns of fMRI signal across visual cortex reflect eccentricity organization

Abstract: The human visual system can be divided into over two-dozen distinct areas, each of which contains a topographic map of the visual field. A fundamental question in vision neuroscience is how the visual system integrates information from the environment across different areas. Using neuroimaging, we investigated the spatial pattern of correlated BOLD signal across eight visual areas on data collected during rest conditions and during naturalistic movie viewing. The correlation pattern between areas reflected the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 99 publications
(214 reference statements)
4
62
1
2
Order By: Relevance
“…Similar observations have been made for maps of activity across cat primary visual cortex (5,46,47), where activity patterns in the absence of visual stimulation reproduce fine-scale functional organization. Between visual areas, multiple studies have demonstrated retinotopically specific patterns of connectivity across hemispheres in both monkeys and humans (7,(9)(10)(11), and human studies have demonstrated differential connectivity within distinct visual pathways (12). Our study helps to link the fine-scale organization of intrinsic activity within areas, with that of the largescale study of coupling between areas by investigating the fine temporal and spatial dynamics of interareal coupling within the visual system.…”
Section: Discussionmentioning
confidence: 95%
“…Similar observations have been made for maps of activity across cat primary visual cortex (5,46,47), where activity patterns in the absence of visual stimulation reproduce fine-scale functional organization. Between visual areas, multiple studies have demonstrated retinotopically specific patterns of connectivity across hemispheres in both monkeys and humans (7,(9)(10)(11), and human studies have demonstrated differential connectivity within distinct visual pathways (12). Our study helps to link the fine-scale organization of intrinsic activity within areas, with that of the largescale study of coupling between areas by investigating the fine temporal and spatial dynamics of interareal coupling within the visual system.…”
Section: Discussionmentioning
confidence: 95%
“…Despite this, the relevance of spontaneous correlations to the finer scales of organization that underlie cognitive representations has not been determined. Some aspects of finescaled organization in sensory cortex are reflected in spontaneous correlation structure, including retinotopic eccentricity biases (19) and orientation maps (20). Analyses that identify discontinuities in spontaneous correlation structure have also been applied in PFC to characterize areal boundaries (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of spontaneous correlations have been used to identify multiple large-scale functional networks (4,5,15) and boundaries between functional areas (2,(16)(17)(18) in human and nonhuman primate association cortex. The spontaneous correlation structure also mirrors established fine-scaled principles of functional organization in visual cortex, such as preferences for retinotopic position (19) and stimulus orientation (20). We therefore leveraged spontaneous activity to examine the finescaled functional organization of human PFC.…”
mentioning
confidence: 99%
“…For example, the human visual cortex shows widely spread and highly structured spontaneous BOLD fluctuations in the absence of visual inputs (e.g., Arcaro et al, 2015;Nir et al, 2006). The structure of the spontaneous fluctuations appears to be highly informative and likely reflects the statistics of the natural environment and cognitive traits (Berkes et al, 2011;Harmelech and Malach, 2013).…”
Section: Introduction: Two Modes Of Cortical Functionmentioning
confidence: 98%